Plan de negocios para implementar una empresa de servicios infantiles en Quito - Carrera Paredes, Christian Napoleón (2018)
It seeks to implement a company dedicated to the organization of children events in the city of Quito, in order to support parents in organizing children parties creating unforgettable experiences for their children; the service will be aimed at people from the urban sector of the upper and upper middle class city of Quito. Magic Events will have facilities located in Veintimilla and December 6, will have three exclusive rooms for children parties, a recreational area for competitions, games, jumpers, snack machines, and entertainers with great experience in magic shows, puppets and recreation, to transmit to children from 1 to 11 years of age unparalleled moments. Magic Events has direct competition from companies like Magic Kingdom, Chikis and Brinkis that have facilities and trajectory in the market, however Magic Events will differentiate itself in the constant innovation of different themes, to experience the children favorite character in an almost real way , generating in the children the desire to repeat the party and the satisfaction of the parents, to receive a quality service and constant care of their children through the provision of nursery services that will ensure that children do not suffer serious falls or accidents. The initial investment of the project is 101.863,54 dollars, with a share capital of 45.000 dollars and a bank loan of 56.863,54 dollars, funded at 5 years, with an annual interest rate of 11,23 percent and aiming for annual growth of sales of 6 percent. The financial analysis shows that the VAN and the TIR are 30.706,13 and 20 percent respectively, being a profitable project for investors and showing their feasibility of implementation.